Survival Data and Predictors of Functional Outcome an Average of 15 Years after the Fontan Procedure: The Pediatric Heart Network Fontan Cohort. (17th June 2014) - Atz, Andrew M.; Zak, Victor; Mahony, Lynn; Uzark, Karen; Shrader, Peter; Gallagher, Dianne; Paridon, Stephen M.; Williams, Richard V.; Breitbart, Roger E.; Colan, Steven D.; Kaltman, Jonathan R.; Margossian, Renee; et al.
Abstract Objective Multicenter longitudinal outcome data for Fontan patients surviving into adulthood are lacking. The aim of this study was to better understand contemporary outcomes in Fontan survivors by collecting follow‐up data in a previously well‐characterized cohort. Design Baseline data from the Fontan Cross‐Sectional Study (Fontan 1) were previously obtained in 546 Fontan survivors aged 11.9 ± 3.4 years. We assessed current transplant‐free survival status in all subjects 6.8 ± 0.4 years after the Fontan 1 study. Anatomic, clinical, and surgical data were collected along with socioeconomic status and access to health care. Results Thirty subjects (5%) died or underwent transplantation since Fontan 1. Subjects with both an elevated (>21 pg/mL) brain natriuretic peptide and a low Child Health Questionnaire physical summary score (<44) measured at Fontan 1 were significantly more likely to die or undergo transplant than the remainder, with a hazard ratio of 6.2 (2.9–13.5). Among 516 Fontan survivors, 427 (83%) enrolled in this follow‐up study (Fontan 2) at 18.4 ± 3.4 years of age. Although mean scores on functional health status questionnaires were lower than the general population, individual scores were within the normal range in 78% and 88% of subjects for the Child Health Questionnaire physical and psychosocial summary score, and 97% and 91% for the SF‐36 physical and mental aggregate score, respectively. Since Fontan surgery, 119 (28%) had additional cardiac surgery; 55% of these (n = 66) in the interim between Fontan 1 and Fontan 2. A catheter intervention occurred in 242 (57%); 32% of these (n = 78) after Fontan 1. Arrhythmia requiring treatment developed in 118 (28%) after Fontan surgery; 58% of these (n = 68) since Fontan 1. Conclusions We found 95% interim transplant‐free survival for Fontan survivors over an average of 7 years of follow‐up. Continued longitudinal investigation into adulthood is necessary to better understand the determinants of long‐term outcomes and to improve functional health status.